Sodium ion-substrate symport in a marine bacterium. - Niven, D F (1980)
Anaerobic suspensions of Alteromonas haloplanktis accumulated alpha-aminoisobutyric acid, by a sodium-dependent process, in response to an artificially imposed membrane potential in the presence or absence of a transmembrane chemical gradient of sodium. These results suggest that the transport of alpha-aminoisobutyrate by this organism occurs via Na+-substrate symport.